A kind of multilevel authentication system for multiple-image by modulated real part synthesis and iterative phase multiplexing. Issue 7 (11th April 2016) - Pan, Xuemei; Meng, Xiangfeng; Wang, Yurong; Yang, Xiulun; Peng, Xiang; He, Wenqi; Dong, Guoyan; Chen, Hongyi
Abstract : A kind of multilevel authentication system for multiple-image based on modulated real part synthesis and iterative phase multiplexing in the Fresnel domain is proposed. In the design process of the low-level authentication system, a series of normalized real part information are iteratively generated by phase retrieval algorithm in the Fresnel domain, and the final private keys for different individual low-level certification images can be fabricated by binary amplitude modulation, superposition, synthesis, and sampling; while in the design process of the high-level authentication system, the final private keys for different individual high-level certification images can be generated by iterative phase information encoding and multiplexing. During the high-level authentication, the meaningful certification image can be reconstructed by the inverse Fresnel transform with the corresponding correct private keys, meanwhile, the correlation coefficient is utilized as judgment criterion; while in the low-level authentication, with the help of correct keys, the noise-like image with meaningless information can be recovered, but a remarkable peak output in the nonlinear correlation coefficient can be generated, which is adopted as the criterion to judge whether the low-level authentication is successful or not. Theoretical analysis and numerical simulations both verify the feasibility of the proposed method.